Images of the body in India - Michaels, Axel; Wulf, Christoph (Taylor and Francis, 2011)
This book engages with the concept of the body in its cultural context by acknowledging and demonstrating that the human body is understood differently in Western and Indian cultures. The contributors show that any attempt to put forward a single concept of the body within Indian culture would be misleading
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Körper; Kunst; Indien; Literatur; Ritus; Hinduismus